Level and correlations of soluble suppression of tumorigenicity 2 protein in heart failure and its relationship with clinical and paraclinical characteristics of patients - A. Ya. Kravchenko; A. V. Budnevsky; A. V. Kontsevaya; T. A. Chernik; R. E. Tokmachev (Российский кардиологический журнал, 2022)
Aim. To establish the correlations of the soluble suppression of tumorigenicity 2 protein (sST2) and N-terminal pro-brain natriuretic peptide (NT-proBNP) with some clinical and paraclinical characteristics of patients with heart failure (HF).Material and methods. The study included 130 patients with HF (men — 54, women — 76, mean age, 64,3±8,3 years) from the regional registry of HF patients in the Voronezh Oblast. All patients underwent echocardiography and general clinical investigations. In addition, the serum levels of sST2 and NT-proBNP were determined and their correlations with other parameters were studied.Results. The blood level of sST2 in HF patients was 339,8 [266;405] pg/ml. In the study sample of patients with HF, sST2 levels correlated with right atrial (r=0,49) and right ventricular (r=0,32) sizes, left ventricular end-diastolic dimension (r=0,34) and volume (r=0,33), left ventricular early diastolic filling rate (r=-0,35), blood calcium level (r=-0,55) and functional class of exertional angina (r=-0,37).Conclusion. The data obtained may indicate a pathogenetic relationship between sST2 and systolic and diastolic dysfunction of the left ventricle and right heart.